Two-year Comparative Outcomes of MIS Lateral and MIS Transforaminal Interbody Fusion in the Treatment of Degenerative Spondylolisthesis: Part I: Clinical Findings. (April 2016) - Sembrano, Jonathan N.; Tohmeh, Antoine; Isaacs, Robert
Abstract : Study Design: A prospective, multicenter, institutional review board (IRB) approved study with randomized and observational study arms. Objective: The purpose of this study was to compare clinical outcomes between minimally invasive transforaminal (MIS TLIF) and MIS lateral interbody fusion (XLIF) in the treatment of patients with low-grade degenerative spondylolisthesis with stenosis through two years postoperative. Summary of Background Data: Few reports exist comparing different MIS approaches directly in the treatment of similar pathology, as most studies report differences between MIS and open procedures. Methods: A total of 55 patients undergoing surgical treatment for degenerative spondylolisthesis with spinal stenosis at one or two contiguous levels between L1 and L5 were enrolled. Twenty-nine patients were treated with XLIF and 26 patients were treated with MIS TLIF. Results: Operative time and length of stay were similar between the XLIF and MIS TLIF groups (171 vs 186 minutes; two days for each group). Blood loss was significantly lower in the XLIF group, with 79% of XLIF cases and 27% of MIS TLIF cases resulting in <100 mL of blood loss, P < 0.001. Hip flexion weakness was more common in the XLIF group (31%) than in the MIS TLIF group (0%). One patient in the XLIF group had a new distal motor weakness and three patients in the XLIF group and two patients in the MIS TLIF group had new sensory changes postoperatively, all of which resolved by 12 months postoperative. Back and leg pain for both XLIF and MIS TLIF groups improved significantly from baseline to 24 months postoperative, with 73% improvement in the XLIF and 64% in the MIS TLIF group. Worst leg pain showed similar improvements through two years postoperative, with a 79% decrease seen in the XLIF group and 74% in the MIS TLIF group. Disability (ODI) improved 53% in the XLIF group and 57% in the MIS TLIF group. Conclusion: Despite different mechanisms of action (indirect vs direct decompression), mid-term clinical outcomes between XLIF and MIS TLIF were similar. These two-year results suggest that both XLIF and MIS TLIF are reasonable MIS approaches for the treatment of lumbar degenerative pathology. Level of Evidence: 2